Seventeenth Century London Midwives: Their Training, Licensing and Social Profile - Evenden-Nagy, Doreen (My University, 1991)
This study is an exploration of seventeenth-century London midwives which is based, for the most part, on seventeenth-century archival sources. It is a study which challenges current and firmly entrenched perceptions of these women. The core of the thesis focuses on seventy-six midwives drawn from twelve parishes who have been examined within the context of their repective parishes. In addition, an index containing the names and other relevant information pertaining to some 900 midwives has been compiled. We will demonstrate by an investigation of the ecclesiastical licensing process, pre-licensed experience, midwives' clients, and the midwives' socio-economic circumstances, that London midwives in the Tudor-Stuart period were not incompetent and poor. Midwives were highly skilled and thoroughly experienced through their participation in a system of unofficial apprenticeship. They were, moreover, well respected both within their own parishes and by clients drawn from a broad spectrum of geographic and socio-economic settings. Many midwives were well-to-do and were the wives or widows of prosperous and influential parishioners. Throughout the seventeenth century London midwives made a valued and important contribution to the City's inhabitants who faced the perils and pleasures of childbirth.
Keywords: History; History